MAPPING OF ELECTRICAL ENERGY SOURCES AND COMPARISON WITH ABROAD - Abdusali Samatovich Suyunov; Shukhrat Abdusalievich Suyunov; Shahruz Khudaykulov; Kamola Boratovna Rakhmatullaeva; Muyassar Isakov (European Science Publishing, 2024)
The article examines regional and local level database on the use of alternative energy sources by mapping alternative energy sources based on foreign experiences. Development of maps, collection of statistical data on wind, solar, small water flows, geothermal sources, use of alternative energy sources, and natural and socio-economic indicators are schematized on thematic maps. The results of scientists who are currently conducting certain scientific research on the use of alternative energy sources in our country have been analyzed.
Keywords: alternative energy, GIS, NREL USA, electronic database, thematic layers and electric power.